2017 ops salary survey : tools, trends, titles : what pays (and what doesn't) for IT operations and DevOps professionals - Suda, Brian (O'Reilly Media, 2017)
Get a clear picture of what operations professionals do, what they're paid, how they're seen within their companies, and how they rate different aspects of their jobs. This report provides the complete results of O'Reilly Media's first annual Ops Salary Survey, including helpful insights into the skills, tools, experience, and responsibilities that most affect Ops salaries throughout the world. Based on more than 650 respondents from 56 different countries and 40 US states, this inaugural survey found that, although Ops are crucial for keeping an organization's technical infrastructure up and running, the roles and duties performed by Ops professionals vary widely by company, industry, geography, and infrastructure type. This report reveals: The median salary of all survey respondents Where Ops professionals are likely to earn higher salaries How company size and team size affect Ops salaries The range of programming languages and operating systems used The types of professionals that Ops people typically work with How respondents rate their work-life balance as Ops professionals How often a respondent's company deploys to production The percentage of companies that still use standard data centers.